Determinan Kejadian Infeksi Saluran Pernapasan Akut pada Balita di Provinsi Jambi (Analisis Data SKI tahun 2023): Determinants of the Incidence of Acute Respiratory Infection in Toddlers in Jambi Province (Analysis of SKI Data in 2023) - Sembiring, Santha Remicha Br Sembiring; Sitanggang, Hendra Dhermawan; Syukri, Muhammad; Butar Butar, Marta; Fitri, Adelina (JURNAL ILMU DAN TEKNOLOGI KESEHATAN TERPADU, 2025)
ARI is an acute infection found in the upper respiratory tract, which includes the nose, sinuses, and throat, and the lower respiratory tract, which includes the bronchi and lungs. Bacteria, viruses, and fungi can cause it. This study used a cross-sectional design with an analytic approach and used secondary data from the SKI in 2023. Analysis was carried out univariate, bivariate, and multivariate. The prevalence of ARI among children under five was 11,95%. Factors associated with the incidence of ARI among children under five in Jambi Province were smoking (p-value = 0,000, PR= 1,89 95% CI: 1,38 – 2,58). Factors not associated with ARI were age, sex, birth weight, immunization status, nutritional status, floor type cooking fuel, maternal education, mother's occupation, and economic status. The dominant factor with ARI incidence was immunization status after controlling for the variables of nutritional status, maternal occupation and the presence of smokers. Therefore, more effective prevention efforts are needed, such as educating parents about the importance of adequate basic immunization and implementing a no-smoking policy in the residential environment.